Redefining chronic mountain sickness: insights from high-altitude research and clinical experience - Zubieta-Calleja Gustavo (Medical Review, 2025)
Chronic Mountain Sickness (CMS), characterized by increased red blood cells above average values traditionally attributed to chronic hypobaric hypoxia exposure, is being redefined in light of recent research and clinical experience. We propose a shift in perspective, viewing CMS not as a singular entity but as Poly-erythrocythemia (PEH), as the Hematocrit/Hemoglobin/Red Blood Cells (Ht/Hb/RBCs) increase constitutes a sign, not a disease reflecting a spectrum of oxygen transport alterations in multiple diseases in the chronic hypoxia environment in high-altitude populations. Drawing on over five decades of experience at the High Altitude Pulmonary and Pathology Institute (HAPPI-IPPA) in Bolivia, we advocate for altitude-specific blood parameter norms and emphasize the importance of correct etiological diagnosis for effective management. This updated understanding not only aids in managing chronically hypoxemic patients at various altitudes but also offers valuable insights into global health challenges, including the recovery from COVID-19.